Cryptocurrency adoption in e-payment: barrier of its implementation - Conde, Naby Nouhou; Abubakar, Adamu; Idris, Norbik Bashah; Mohd Mohadis, Hazwani (Little Lion Scientific, 2021)
Cryptocurrency is a type of cryptographic e-currency generated by the computational result of mathematical techniques throughout blockchain technology. It has bitcoin as the world's first decentralized anonymous digital currency which allows online transactions without relying on any third-party institutions or government. Though, its technology is considered as one of the secure online integrated payment systems in financial transactions for many different businesses, it is still struggling for its integration and people are reluctant to embrace its adoption. Therefore, to address this gap, we discussed several implications for theory within information system adoption in light with the study’s objective. the research utilized a quantitative method survey built on theories of Technological Acceptance Model (TAM), Theory of Reasoned Action (TRA), Delone and McLean Information System Success Model and Self-determination Theory Model (SDT) to examine the factors influencing its adoption in e-payment. We used a sample of 402 participants for the analysis where seven main variables and nine hypotheses got formulated and tested using PLS-SEM path modeling with SPSS. The result shows that the analysis of the data provided support for all the hypotheses and established a positive relation between variables and the findings obtained have both academic and practical worth in terms of Information Systems technology adoption for improving the understanding of factors influencing cryptocurrency adoption in e-transaction